2010
DOI: 10.1590/s0034-737x2010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade de propágulos de morangueiro em diferentes concentrações de nitrogênio no cultivo sem solo

Abstract: Production and quality of strawberry transplants in different nitrogen concentrations in soilless growing systemThe objective of this work was to evaluate the effects of nitrogen concentration on the production and quality of strawberry bare root transplants and runner tips in soilless growing system. Stock plants were planted on September 13 th , 2007. Transplants were harvested on February 18 th , 2008. Nitrogen concentrations of 8, 11, 14 and 17 mmol L -1 in the nutrient solution were evaluated. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
5
0
6
Order By: Relevance
“…In this study, only first order runner tips bearing one expanded leaf were collected and its crown diameter was higher than that reported by Oliveira et al (2010) and Giménez et al (2008). These authors used a growing sand bed for simultaneously producing bare root transplants on the bed surface and runner tips on suspended stolons growing downward between beds.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, only first order runner tips bearing one expanded leaf were collected and its crown diameter was higher than that reported by Oliveira et al (2010) and Giménez et al (2008). These authors used a growing sand bed for simultaneously producing bare root transplants on the bed surface and runner tips on suspended stolons growing downward between beds.…”
Section: Resultsmentioning
confidence: 95%
“…Present results agree with Durner et al (2002), to whom runner tips collected in weekly intervals are bigger and lead to more uniform transplants. According Oliveira et al (2010) , no difference was found in emission of runner tips at N concentrations from 8 to 17 mmol L -1 and it was attributed to competition for assimilates between plant and runner tip growth, as final plant density by mother and daughter plants on the bed surface reached 339 plants m -2 . In the present experiment, plant density was of 12 plants m -2 and stolons were not kept to grow, as a way to reduce such competition.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Em relação à massa seca de raiz, observou-se maiores reduções com a omissão dos macronutrientes (P, K, N, Ca e Mg). O fato do N reduzir a massa da raiz já era esperado, pois esse elemento é requerido em grande quantidade pelas culturas agrícolas e é o mais limitante para o crescimento e desenvolvimento das plantas (OLIVEIRA et al, 2010). O Mg tem como função ativar ou reguladar várias quinases, ATPases, carboxilase/oxigenase RuBP e outras enzimas do metabolismo de carboidratos (MARSCHNER, 2012) e dessa forma, a falta deste nutriente pode causar a redução do crescimento das raízes (YANG et al, 2013;CAKMAK, 2013).…”
Section: Resultsunclassified
“…O morangueiro (Fragaria x ananassa Duch.) é uma espécie cultivada em todo o mundo e a área de produção aumenta a cada ano (PALENCIA et al, 2010), em razão de ser uma fruta apreciada pelos consumidores, devido a coloração, aroma, sabor (GIMÉNEZ et al, 2008) e por ser considerada fonte de vitaminas e minerais (SINGH et al, 2010). No Brasil a área de produção é de aproximadamente 4 mil hectares e 120 mil toneladas de frutas (KIRSCHBAUM et al, 2017).…”
Section: Introductionunclassified